Metabolic and Endocrine Disorders in Pseudarthrosis. Issue 5 (June 2019) - Hills, Jeffrey M.; Khan, Inamullah; Archer, Kristin R.; Sivaganesan, Ahilan; Daryoush, Joshua; Hong, Daniel Y.; Dahir, Kathryn M.; Devin, Clinton J.; Stephens, Byron
Abstract : Study Design: Retrospective Cohort. Objective: Establish 1-year patient-reported outcomes after spine surgery for symptomatic pseudarthrosis compared with other indications. In the subgroup of pseudarthrosis patients, describe preexisting metabolic and endocrine-related disorders, and identify any new diagnoses or treatments initiated by an endocrine specialist. Summary of Background: Despite surgical advances in recent decades, pseudarthrosis remains among the most common complications and indications for revision after fusion spine surgery. A better understanding of the outcomes after revision surgery for pseudarthrosis and risk factors for pseudarthrosis are needed. Methods: Using data from our institutional spine registry, we retrospectively reviewed patients undergoing elective spine surgery between October 2010 and November 2016. Patients were stratified by surgical indication (pseudarthrosis vs. not pseudarthrosis), and 1-year outcomes for satisfaction, disability, quality of life, and pain were compared. In a descriptive subgroup analysis of pseudarthrosis patients, we identified preexisting endocrine-related disorders, frequency of endocrinology referral, and any new diagnoses and treatments initiated through the referral. Results: Of 2721 patients included, 169 patients underwent surgery for pseudarthrosis. No significant difference was found in 1-year satisfaction between pseudarthrosis and nonpseudarthrosis groups (77.5% vs. 83.6%, respectively). A preexisting endocrine-related disorder was identified in 82% of pseudarthrosis patients. Endocrinology referral resulted in a new diagnosis or treatment modification in 58 of 59 patients referred. The most common diagnoses identified included osteoporosis, vitamin D deficiency, diabetes, hyperlipidemia, sex-hormone deficiency, and hypothyroidism. The most common treatments initiated through endocrinology were anabolic agents (teriparatide and abaloparatide), calcium, and vitamin D supplementation. Conclusions: Patients undergoing revision spine surgery for pseudarthrosis had similar 1-year satisfaction rates to other surgical indications. In conjunction with a bone metabolic specialist, our descriptive analysis of endocrine-related disorders among patients with a pseudarthrosis can guide protocols for workup, indications for endocrine referral, and guide prospective studies in this field.